Transcription factor Nrf2 regulates SHP and lipogenic gene expression in hepatic lipid metabolism - Huang, Jiansheng (American Physiological Society, 2010)
Nuclear factor erythroid-2 related factor 2 (Nrf2) plays a pivotal role in cytoprotection against both endogenous and exogenous stresses. Here, we establish a novel molecular link between Nrf2, nuclear receptor small heterodimer partner (SHP; NROB2), lipogenic genes, and hepatic lipid homeostasis. Deletion of Nrf2 (Nrf2(−/−)) in mice resulted in a reduced liver weight, a decrease in fatty acid content of hepatic triacylglycerol, as well as concomitant increases in the levels of serum VLDL-triglyceride (TG), HDL cholesterol, and ketone bodies at 6 mo of age. Liver weight and hepatic TG content were consistently lower in Nrf2(−/−) mice upon a high-fat challenge. This phenotype was accompanied by downregulation of genes in lipid synthesis and uptake and upregulation of genes in lipid oxidation in older Nrf2(−/−) mice. Interestingly, SHP expression was induced with age in Nrf2(+/+) mice but decreased by Nrf2 deficiency. Forced expression and activation of Nrf2 by Nrf2 activators consistently induced SHP expression, and Nrf2 was identified as a novel activator of the SHP gene transcription. We also identified PPAR-γ, Fas, Scd1, and Srebp-1 as direct targets of Nrf2 activation. These findings provide evidence for a role of Nrf2 in the modulation of hepatic lipid homeostasis through transcriptional activation of SHP and lipogenic gene expression.